Pendampingan Pembelajaran Ilmu Tajwid Di Tpq Al-Jinani Dusun Dadapan Desa Salen Kecamatan Bangsal Kabupaten Mojokerto - Khikmiyah, Siti Khikmiyah; Munfa'ati, Kusnul Munfa'ati; Shafira Fairuzza Rahmi; Jannah, Karismatul; Anjasmara, Pada; Izat, Ilham Aliza (LPPM, STAI Al-Azhar Menganti, 2023)
The community empowerment program related to mentoring learning tajwid using the numbered-heads together (NHT) learning strategy accompanied by flash card media aims to improve the ability to read the Qur'an in accordance with the rules of tajwid science and foster a new enthusiasm in learning tajwid science using the numbered-head strategy together (NHT) along with flash card media. The research method used is Asset Based Community Development or more familiarly known as the ABCD research method. The ABCD research method is one of the approaches in efforts to develop society. The 5 stages of the ABCD method, namely from the Define, Discovery, Dream, Design or Implement and Control or Evaluate (Deliver or Destiny) stages. The community empowerment program ii can run well and smoothly. The results of the study showed that the ability of TPQ Al-Jinani students to read the Qur'an in accordance with the rules of tajwid science which was initially still relatively low, after the mentoring was held it seemed to have increased. Apart from that, the students also looked enthusiastic in participating in tajwid learning activities. This means that tajwid learning assistance using the numbered-heads together (NHT) learning strategy accompanied by flash card media at TPQ Al-Jinani has a positive impact on overcoming learning problems.